(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2024)
When listening to song, the body reduce the production of the hormone cortisol so it can deal with stress and depression. The rise of songs that use words that have hidden meanings makes the listener less understand the meaning of the song. As a result, the purpose of this research is to clarify the types of meaning and types of figurative language meaning. The goal of this research is to determine what types of meaning and types of figurative language meaning in the song “Traitor’’ by Olivia Rodrigo. To provide an accurate rendering of issue recognized, a descriptive qualitative approach is used. The data is taken from the lyrics of the song “Traitor’’ by Olivia Rodrigo. The results of the research show that there were three types of semantic meaning which had been used in the song "’Traitor" namely connotative meaning, conceptual meaning and associative meaning. And there are four types of figurative language meanings used in the song "Traitor" namely simile, personification, metaphor, and paradox.